Enhanced Catalytic Activity of Fe Phthalocyanines Linked to Au(111) Via Conjugated Self-Assembled Monolayers of Aromatic Thiols for o2 Reduction - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Caroli-Rezende, M; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Silva-Rojas, J; Silva-Rojas, J; Ponce-Hormazabal, I; Onate, R (2011)
Sin Editorial Disponible